The Influence of Internal Control Systems and Understanding of Accounting Information Systems on Financial Performance - Dadang Abdullah; Siti Asmanah (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
This study aims to analyze the influence of internal control systems and accounting information systems on financial performance. The object of the research is the management of the Muhammadiyah Banten regional leadership. This study was conducted on 78 respondents using a quantitative descriptive approach. The data collection method uses the survey method with research data collection instruments are questionnaires through Google Form. The approach used in this study is the Structural Equation Model (SEM) with Smart Partial Least Square (PLS) analysis tools, validity tests, reliability tests and hypotheses of all scales are declared valid. This study proves that the internal control system has a significant effect on financial performance, the accounting information system has a significant effect on financial performance